Hiroshima after Iraq : three studies in art and war - Deutsche, Rosalyn (Wellek Library lectures at the University of California, Irvine., 2010)
"Many on the left lament an apathy or amnesia toward recent acts of war. Particularly during the George W. Bush administration's invasion of Iraq, opposition to war seemed to lack the heat and potency of the 1960s and 1970s, giving the impression that passionate dissent was all but dead. Through an analysis of three politically engaged works of art, [author] argues against this melancholic attitude, confirming the power of contemporary art to criticize subjectivity as well as war."--Jacket